PERKEMBANGAN TEORI AKUNTANSI: TINJAUAN LITERATURE TERPILIH - Muhammad Arfan Harahap; Saparuddin Siregar (ITB AAS INDONESIA, 2022)
This study aims to explain the definition of accounting theory. In this case, it is more focused on positive accounting theory and normative accounting theory. The author uses sources from selected research journals. The conclusion of this research is that theory is often used as the basis for an action or practice. In its development, accounting theory is divided into four periods of accounting theory. The first period is called the Pre-Theory period 1492-1800. The second period is called the Pragmatic accounting period or the general scientific period from 1800-1955. Furthermore, the third period is referred to as the normative period 1956-1970. The last period and lasts until now is called the period of positive accounting theory which began in 1970. Normative accounting theory is a statement that is needed in accounting practice, normative accounting theory focuses on norms and is not intended for theory development. While positive accounting theory seeks to explain and predict phenomena related to accounting. Using an approach derived from positivism, empirical accounting research is developed to support and justify various accounting methods or practices in the real world.